Data on climate change effect and use of adaptation strategies among smallholder maize farmers: Evidence from a microlevel survey in Ehlanzeni District, South Africa - Chrescewell Sanele Nkosi; Oluwasogo David Olorunfemi; Humphrey Khwidzhili (Data in Brief, 2023)
Climate Change and its effects on agriculture and human survival remain a global concern requiring continual research and the use of coping strategies. This paper focus on presenting a data article on climate change effect and use of adaptation strategies by exploiting the insight from a microlevel survey carried out among smallholder maize farmers in South Africa. The data present the change in maize output and income farmers have experienced in the last two growing seasons attributed to the effect of climate change, climate change adaptation and mitigation strategies currently utilized, and constraints faced by the maize farmers. The collected data were analyzed using descriptive statistics and t-Test analysis. The findings revealed that climate change effect is very evident in the area by the significant reduction in output and income observed among the maize farmers, and thus, it is still pertinent for farmers to scale-up their use of adaptation and mitigation strategies in the area. However, the farmers can only effectively and sustainably achieve this if extension agencies provide continuous climate change-related training for maize farmers and government harmoniously work with improved seed production agencies to ensure smallholder maize farmers can adequately access seeds when needed and at subsidized rates.